Special Education: What it is and why we need it - Kauffman, James M.; Hallahan, Daniel P. (Boston, 2005)
The concept is not merely sound but essential to universal education in a democratic and benevolent society. Special education is a powerful concept, which leaves it open to strong opinions in support and in opposition. And it is a complex practice, which sometimes results in it being practiced poorly, and, in many instances, superbly. Our intention is to help readers understand both the integrity of the concept of special education and the characteristics of good practices.
Keywords: Special Education-United States